A Prescription for Change : the Looming Crisis in Drug Development - Kinch, Michael, 1966- (The Luther H. Hodges Jr. and Luther H. Hodges Sr. Series on Business, Entrepreneurship, and Public Policy Ser., 2018)
Annotation